1980
DOI: 10.1007/bf02273085
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical decomposition of 1,4-benzodiazepines

Abstract: By labelling chlordiazepoxide and diazepam with t4C it was possible to follow quantitatively the photochemical decomposition of these compounds. It was found for chlordiazepoxide that the wavelength of light does not determine the character, but only the concentrations of the products formed.On irradiation of chlordiazepoxide, dissolved in methanol or methanol-water (pH=7.4), an oxaziridine is formed, which is subsequently converted into a quinoxaline and a benzoxadiazocine derivative. However, by irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This compound was identified previously when methanolic solutions of diazepam were exposed to UV radiation. 16 Peak III was identified as 2-amino-5-chlorobenzophenone in a similar manner; by comparison with the retention times and mass spectra (MS 1−3 ) of an authentic standard of 2amino-5-chlorobenzophenone (SI Figure 5S). Solutions of pure I and III in water were also irradiated herein and the rate constants and half-lives determined (ref 25; Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This compound was identified previously when methanolic solutions of diazepam were exposed to UV radiation. 16 Peak III was identified as 2-amino-5-chlorobenzophenone in a similar manner; by comparison with the retention times and mass spectra (MS 1−3 ) of an authentic standard of 2amino-5-chlorobenzophenone (SI Figure 5S). Solutions of pure I and III in water were also irradiated herein and the rate constants and half-lives determined (ref 25; Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…15 The major removal mechanisms for diazepam in water were identified as sorption to sedimenting particles, dilution, advection, and importantly, rapid photodegradation in the superficial layers. 11 However, the only available data for photolysis were derived from a study of diazepam in methanol irradiated with 254 nm (UV) wavelength radiation of unspecified intensity 16 and a reference to one of our own unpublished preliminary experiments (cited by Straub). 11 A review 17 conducted in 2003 summarizing the existing literature concerning the photochemical behavior of many pharmaceuticals concluded that with some exceptions, the environmental photochemistry of the vast majority of pharmaceuticals had not been studied adequately.…”
Section: ■ Introductionmentioning
confidence: 99%
“…nitrazepam. 31 For a study of the stability of six drugs and one metabolite in blood, see Giorgi and Meeker. 32 Temperature Several studies have addressed the effect of temperature on stability.…”
Section: Redistribution Between Cells and Plasma/serummentioning
confidence: 99%
“…The alkylenethioxanthines flupenthixol (89), clopenthixol(90), thiotixene (9 1) and chlorprothixene (92) are used as E j z isomeric mixtures. The E L ratio changes upon irradiation (>300 nm, see Among phenothiazines, chlorpromazine (94) has been extensively investigated (see Scheme 30).…”
Section: Xhioxanthine and Phenothiazine Psychotherapeutic Agentsmentioning
confidence: 99%